1974
DOI: 10.1007/bf00155254
|View full text |Cite
|
Sign up to set email alerts
|

Brittle fracture of solids with arbitrary cracks

Abstract: A B S T R A C TOne of the problems of fracture mechanics is the prediction of the propagation of cracks in solids. Thepresent paper deals mainly with linear fracture mechanics which owes its origin to the works erA. A. Griffith [1,2] and studies the development of cracks under sufficiently low loads when the behaviour of the material within a region sufficiently remote from the edges of cracks may he regarded as linearly elasti~ At present, linear fracture mechanics [3] is restricted mainly to special kinds of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
185
0
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 399 publications
(189 citation statements)
references
References 13 publications
3
185
0
1
Order By: Relevance
“…In 2D and under quasi-static conditions, v c R , it has been shown that the Principle of Local Symmetry [93] offers good approximations for crack paths [94][95][96][97][98][99][100]. This approximation suggests that under quasi-static conditions, and under the assumption that no intrinsic length scales exist near the tip, crack propagation along smooth paths will annihilate any shear (mode II) component of the fields ahead of the tip.…”
Section: Understanding 2d Instabilitiesmentioning
confidence: 99%
“…In 2D and under quasi-static conditions, v c R , it has been shown that the Principle of Local Symmetry [93] offers good approximations for crack paths [94][95][96][97][98][99][100]. This approximation suggests that under quasi-static conditions, and under the assumption that no intrinsic length scales exist near the tip, crack propagation along smooth paths will annihilate any shear (mode II) component of the fields ahead of the tip.…”
Section: Understanding 2d Instabilitiesmentioning
confidence: 99%
“…Griffith's energy criterion (Griffith, 1920;Freund, 1990;Broberg, 1999) and the principle of local symmetry (Gol'dstein and Salganik, 1974;Leblond, 1989) imply…”
Section: Stress Field Ahead Of Curved Extensions Of a Branched Crackmentioning
confidence: 99%
“…As shown in (Adda-Bedia, 2004b), the paths of the branches can be determined if each crack tip satisfies the principle of local symmetry during propagation (Gol'dstein and Salganik, 1974). Imposing this (Eq.…”
Section: The Shape Of the Branched Cracksmentioning
confidence: 99%
See 1 more Smart Citation
“…If cracks are under mixed-mode loading, 8 such as tensile and shear stresses, they often propagate in a curved or kinked manner. [9][10][11][12] Under certain conditions, the kinking paths may continue regularly to form various crack patterns. 13,14 For example, two-dimensional spiral or sinusoidal cracks can arise in the dried crusts of aqueous suspensions 15 or in glass slides under gradient temperature fields.…”
Section: Introductionmentioning
confidence: 99%